In the Name of (Un)Sustainability: A Critical Analysis of How Neoliberal Ideology Operates Through Discourses About Sustainable Progress and Equality - Diana Jacobsson (tripleC: Communication, Capitalism & Critique)
This article examines sustainable development discourses while addressing the unsustainable structures within which these discourses take place. The main research question concerns how sustainability is understood in relation to class and capitalism and what ideologies are expressed as neutral in the anodyne context of public information. Critical discourse analysis is applied as a method to examine how sustainable development is shaped through the construction of problems, responsibilities and solutions in a Swedish municipal magazine. The analysis reveals two parallel constructions: hyper-politicised discourses about free enterprise and a trivialisation of discourses about socio-economic challenges. Texts about social care and social responsibility are represented in the form of banal politics, transforming conflict into consensus, while stories about the business sector rely heavily on market rationales stressing the importance of political intervention to increase the attractive power of entrepreneurialism. Taking Critical Theory as its starting point, the analysis discusses the neoliberal paradox, namely that in the neoliberal political regime, despite the rhetoric of individualism and freedom, the role of the state is to support private enterprises. The article argues that the role of communication needs further analytical attention to increase our understanding of how sustainability is shaped and established in mainstream public discourse. It concludes that the specific communication practice examined here promotes neoliberal capitalism by encouraging the continued unsustainable class structuring of our society.